FAKTOR PENGHAMBAT PELAKSANAAN PENGISIAN REKAM MEDIS ELEKTRONIK TERHADAP KINERJA PEGAWAI DI KAMAR BEDAH RS MATA CICENDO - Shalva Aulia Ananda; Annisa Ulfah (LPSDI Bina Patria, 2024)
One important part of the health information system in healthcare facilities is the Electronic Medical Record. The purpose of using electronic medical records is to store and organize patient health data digitally so that the medical team can access information accurately. However, some healthcare facilities still face challenges in implementing an electronic-based medical record system. The purpose of this study was to find barriers to the use of electronic-based medical records. In this study, the method used is a qualitative approach that focuses on direct observation of the factors that hinder the implementation of electronic medical record filling on employee performance in the surgical room. The keywords used were “Electronic Medical Records”, “employee performance”, “barriers”, and “surgical suite”. The results showed that the inhibiting factors for the implementation of electronic-based medical records on employee performance in the operating room were the lack of human resources (HR), the Rm 16 and Rm 17 forms which were still in the hybrid phase, and lack of infrastructure, are the most or dominant obstacles. The result showed that the obstacles in the implementation of electronic-based medical records are mostly caused by the factor of medical record forms that are still in the hybrid phase.